EVALUASI PERENCANAAN SISTEM DISTRIBUSI AIR BERSIH INSTALASI TEGAL GEDE KABUPATEN BEKASI - Nur Ilman Ilyas; Nisa Nurhidayanti; Nasution Nasution (Jurnal Pelita Teknologi, 2020)
Increased population growth must be followed by the availability of clean and healthy water. This research is to find out the amount of water needs of PDAM customers for South Cikarang and Cibarusah areas. The purpose of this paper is to find out the clean water needs of customers of PDAM Tirta Bhagasasi South Cikarang Branch in 2020 and find out the increase in population and number of customers and how much those needs are. So that PDAM Tirta Bhagasasi can serve the community at present and in the future for its distribution evenly, so that the community can obtain clean water smoothly. From the analysis using the realization of needs analysis, it is obtained the need for clean water for customers of PDAM Tirta Bhagasasi, Cikarang Selatan Branch for 2020, amounting to 394, 5 liters / second. Estimated clean water debit needed for 2020 in the Cibarusah region is Q = 169.1 liters / sec. The volume of additional customers for 2020 South Cikarang and Cibarusah Branches is 0.283 m3 / second. With this debit, it is possible to add 31,067 customers to PDAM Cikarang Selatan Branch. In the analysis of the pipe capacity for the next five years 2020 for the South Cikarang Branch the dimension of the pipe is still able to flow water from the Tegal Gede reservoir to the villa Mutiara reservoir.